Konsumerisme Masyarakat Kontemporer Menurut Herbert Marcuse - Theguh Saumantri (Media: Jurnal Filsafat dan Teologi, 2022)
This paper aims to describe the thoughts of the philosopher Herbert Marcuse about the phenomenon of consumerism in contemporary society. The method used is literature research with a philosophical approach. This study finds that there is a paradigm shift in the realm of consumption in the era of contemporary society. According to Marcuse, consumerism in today's society contains a totalitarian logic. The totalitarian tendencies of technology have shaped one-dimensional patterns of thought and behavior. The indication is that society cannot escape the influence and domination of technology. Technology has produced goods in abundance. As a result, the goods produced by the means of production are manipulated and indoctrinated to the needs of individuals in an advanced industrial society.